2017
DOI: 10.1111/icad.12271
|View full text |Cite
|
Sign up to set email alerts
|

Tracking wetland community evolution using Diptera taxonomic, functional and phylogenetic structure

Abstract: Different processes drive spatial variation in community composition. Standard measures of composition are useful in species‐based conservation and ecology, but they may be less informative in the context of evolutionary history and functional diversity. Functional and phylogenetic approaches are increasingly used to test mechanisms driving biodiversity patterns. We studied 28 families of flies (Diptera) with a range of functional characteristics in three wetland classes (bogs, swamps, marshes) in Quebec, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 123 publications
(134 reference statements)
1
4
0
Order By: Relevance
“…Using a morphospecies approach we were able to obtain finer scale identification, but to fully understand community assembly patterns, more identification tools (including molecular techniques) of the broader community (including all invertebrates and fungi) and in-depth life-history information are needed. Our results suggest that Diptera community assembly may be driven by both stochastic and deterministic processes which is in support of recent studies in community assembly ( Gravel et al, 2006 ; Thompson & Townsend, 2006 ; Ellwood, Manica & Foster, 2009 ; Barber & Marquis, 2011 ; Ferrenberg, Martinez & Faist, 2016 ; Grégoire Taillefer & Wheeler, 2017 ). We have also demonstrated that to retain the highest saproxylic Diptera diversity in a forest, a variety of decaying wood types at different stages of decomposition is necessary.…”
Section: Discussionsupporting
confidence: 92%
“…Using a morphospecies approach we were able to obtain finer scale identification, but to fully understand community assembly patterns, more identification tools (including molecular techniques) of the broader community (including all invertebrates and fungi) and in-depth life-history information are needed. Our results suggest that Diptera community assembly may be driven by both stochastic and deterministic processes which is in support of recent studies in community assembly ( Gravel et al, 2006 ; Thompson & Townsend, 2006 ; Ellwood, Manica & Foster, 2009 ; Barber & Marquis, 2011 ; Ferrenberg, Martinez & Faist, 2016 ; Grégoire Taillefer & Wheeler, 2017 ). We have also demonstrated that to retain the highest saproxylic Diptera diversity in a forest, a variety of decaying wood types at different stages of decomposition is necessary.…”
Section: Discussionsupporting
confidence: 92%
“…Since the review of Spitzer & Danks (120), more recent literature has expanded on some of the themes that they developed, with mixed success. The unique environmental conditions and plant communities in peatlands were found to have a stronger control on dipteran assemblages than they did in marshes and swamps (124). Hummock-hollow microtopography was found to control communities of microarthropod decomposers (8).…”
Section: Ecological Controls On Peatland Arthropodsmentioning
confidence: 87%
“…This total may still underestimate the total diversity present, and we demonstrate the importance sampling errors can have for modeling this community. Communities exhibited near-random patterns of spatial and temporal turnover, a property rarely observed in freshwater systems (33). As a result, impacts on the wetland macroinvertebrate community are difficult to establish at local scales because occurrence is weakly related to environmental factors and site composition can fluctuate rapidly over time (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%